What is in a name? How caste names affect the production of situated knowledge. Issue 7 (3rd July 2017) - Patel, Kamna
Abstract: Patel, Desai, Kothari … to those literate in the workings of caste these names describe a network and its power in relation to other networks, they infer the rules of engagement within and between network members, and they ascribe a geographical terrain to home. In research, rules of behaviour and assumptions of place that are coded into names can affect access to respondents, their disclosure of data and subsequent claims to validity. This article explores the coded expectations of knowledge embedded in a name as seen by someone (me) fairly illiterate in the workings of caste by utilising the principle of Bourdieu's doxa – a 'pre-reflexive intuitive knowledge' – to untangle and explore the effect of names on the production of partial and situated knowledge. Drawing on fieldwork in Gujarat, India, I analyse reflexive accounts through the lenses of feminist geographers and critical race scholars to illustrate the effects of being unknowingly and unwillingly placed into a social hierarchy of power in the field, introduce the idea of 'us-ing' (an opposite of othering) to describe researcher-respondent relations, and explore how readers might interpret the presence or absence of data and claims to validity. These accounts make visible the effects of positionality on knowledge production in ways that speak to feminist-postcolonial research, and specifically to feminist researchers of colour conducting research away from 'home'.